Genomics approaches to study the biology underlying resistance to trypanosomiasis--some unexpected lessons - Kemp, Stephen J.; Hanotte, Olivier H.; Agaba, Morris; Noyes, H.A.; Gibson, John P.; Archibald, A.L.; Rennie, C.; Hulme, H.; Brass, A. (2008)
An international multidisciplinary consortium is conducting a programme of research on the host response to trypanosome infection. This builds upon quantitative trait loci (QTL) mapping which identified genome regions influencing susceptibility to pathology following T. congolense infection in both cattle and mice. The approach uses expression analysis to examine the response of both susceptible and resistant strains and a series of novel informatics tools to identify pathways which are activated as a result of challenge, and those which are differentially used by resistant and susceptible strains. Of particular interest are those pathways which simultaneously satisfy both criteria, i.e. are significantly differentially activated and contain genes within QTL regions. However, it is important to stress that it is not required that the genes within the QTL region are differentially expressed themselves.